1999
DOI: 10.1099/0022-1317-80-3-663
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of bovine CD8+ T-cell responses to foot-and-mouth disease virus.

Abstract: The aim of this study was to investigate the importance of cellular immunity in foot-and-mouth disease in cattle, in particular to determine whether a CD8 M T-cell response could be detected, as these cells may play a role in both immunity and virus persistence. As attempts to characterize classical cytotoxic T cells had yielded non-reproducible results, largely due to high backgrounds in control cultures, a proliferation assay was developed that was demonstrated to detect antigenspecific, MHC class I-restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 13 publications
1
46
0
2
Order By: Relevance
“…Anti-class I MAb gave lower inhibitions, in agreement with the previous reports on porcine lymphoproliferation against whole virus (14,45) and FMDV capsid protein peptides (7). These inhibitions might relate to the high proportion of CD8 ϩ CD4 ϩ double-positive cells found in swine (58), dominated by memory Th lymphocytes (50,59).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Anti-class I MAb gave lower inhibitions, in agreement with the previous reports on porcine lymphoproliferation against whole virus (14,45) and FMDV capsid protein peptides (7). These inhibitions might relate to the high proportion of CD8 ϩ CD4 ϩ double-positive cells found in swine (58), dominated by memory Th lymphocytes (50,59).…”
Section: Discussionsupporting
confidence: 90%
“…Despite animal to animal variation, 19 peptides were stimulated in vitro lymphocytes from, at least, four of the six infected pigs analyzed ( Table 2). The responsive peptides define T-cell regions efficiently recognized by swine lymphocytes at the following amino acid positions: 3A and -[121-135], 3B [13][14][15][16][17][18][19][20][21][22][23] and - [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], and 3C [191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210]. Eleven of these peptides were also recognized by lymphocytes from at least three of the five heterotypically reinfected pigs analyzed (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it appears that the T cell responses mediated by CD4 + cells are required for protective immunity against FMDV, by participating in the production of antiviral antibodies [31,58,240] and by maintaining the appropriate microenvironment needed for a synergistic immune response. The induction of FMDV-specific effector cytotoxic T lymphocytes (CTL) has been difficult to evaluate [5,50,190,215]. Recent studies have shown that FMDV infection results in a rapid reduction of MHC class I expression on susceptible cells [216].…”
Section: Immune Responsementioning
confidence: 99%
“…Şap hastalığına karşı korunmada, antikorların rol aldığı ileri sürülmüşse de (32), son yıllarda yapılan immunolojik çalışmalar sonucunda hücre aracılı bağışık-lık cevaplarının, özellikle de T-hücre cevabının önemli olduğu ortaya konmuştur (6,15,20). Virus ile enfeksiyonu ya da aşılamayı takiben, CD4+ ve CD8+ hücreleri içeren spesifik T-hücre aracılı antiviral cevapların şekil-lendiği ve virusun organizmadan uzaklaştırılmasında hücre-aracılı bağışıklığın rol aldığı rapor edilmiştir (5,24).…”
Section: Introductionunclassified